Overexpression of miR-181a regulates the Warburg effect in triple-negative breast cancer. (2nd January 2023) - Wang, Y.; Tahiri, H.; Yang, C.; Gu, M.; Ruan, X.; Hardy, P.
Abstract: Objective: Triple-negative breast cancer (TNBC) is highly aggressive and leads to a poor prognosis. microRNA-181a (miR-181a) exhibits strong antineoplastic effects in many types of cancer. In this study, we examine the responses of human miR-181a-transfected TNBC cells and explore the mechanisms underlying the observed effects. Methods: A series of cellular assays were conducted using cells from the MDA-MB-231 TNBC line to assess the impact of miR-181a overexpression. The extracellular acidification rate, lactate production and glucose uptake were evaluated as a measure of aerobic glycolysis (i.e. the Warburg effect). The expressions of glycolysis-related gene were analyzed. Results: Viability, migration and survival of miR-181a-transfected MDA-MB-231 cells were all significantly reduced. miR-181a inhibited glycolysis in TNBC cells by reducing the rates of glucose uptake and lactate production and a substantial downregulation of factors known to contribute to the Warburg effect, including the serine/threonine kinase, AKT3, hypoxia-inducible factor-1α (HIF-1α) and progesterone receptor membrane component 1 (PGRMC1). Conclusion: Our results demonstrate that miR-181a may regulate glycolysis in MDA-MB-231 TNBC cells, potentially via interference with components of the AKT3–HIF-1α and PGRMC1 pathways. These results suggest that miR-181a might be developed as a therapeutic agent for use in antineoplastic regimens directed at TNBC and PGRMC1-overexpressing breast cancers.